Romans 7 and Christian identity: a study of the 'I' in its literary context - Timmins, Will N. (Society for New Testament studies monograph series, 2017)
In this book, Will N. Timmins provides a close rereading of Romans 7 within its literary-argumentative context and offers a fresh and compelling solution to the identity of the 'I' in this text. Challenging existing paradigms, which fail to provide both literary coherence and theological plausibility, he develops his own positive theory about the device. Along the way he also re-examines a number of key texts within the letter, which have hitherto not been given due weight within the scholarly discussion. This study offers a fresh and satisfying solution to one of the Bible's most notorious cruxes, and contributes to our understanding of the apostle Paul's thought. It will be of interest to all scholars and students within the fields of biblical studies and Christian theology.